Anterior cutaneous neurectomy for chronic abdominal wall pain: A case report and review of the literature - Cory McLaughlin; Artee Gandhi; Chad E. Hamner (Elsevier, 2017)
Chronic abdominal wall pain is a rare, debilitating problem in both children and adults. Anterior cutaneous neurectomy has been shown effective for nerve entrapment, predominantly in adults and mainly outside of the United States. Evidence for the efficacy of surgery in children is very limited, with only three case series in the last decade including a total of 75 patients. We report a case of a 15 year old boy with chronic abdominal wall pain who experienced complete symptomatic relief after neurectomy. We believe this to be only the second report of this procedure in the United States. Additional studies with longer follow-up are needed to better characterize patients that would most benefit from neurectomy and to clarify the extent of surgery necessary to minimize surgical failure.